2012
DOI: 10.2134/agronj2012.0095
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield and Quality in Relation to Soil Properties

Abstract: To optimize management, farmers require quantitative understanding of the factors aff ecting variability in soybean [Glycine max (L.) Merr.] seed yield and quality. Our objectives were to characterize spatial variation in soybean seed yield, oil concentration, and protein concentration in two south-central Minnesota fi elds over 6 yr of a corn [Zea mays L.]-soybean rotation, and to determine the infl uence of fertilizer treatments, soil chemical properties, and topography on soybean yield, oil, and protein. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
(106 reference statements)
3
27
1
Order By: Relevance
“…Yield and quality parameters of soybean are affected by many factors, but the appropriate interaction of soil and climatic factors that already exist at the regional level (Anthony et al 2012), is essential.…”
mentioning
confidence: 99%
“…Yield and quality parameters of soybean are affected by many factors, but the appropriate interaction of soil and climatic factors that already exist at the regional level (Anthony et al 2012), is essential.…”
mentioning
confidence: 99%
“…Shoot or seed dry weight reached a plateau at high P application treatments. Anthony et al (2012) showed that the soybean yield was optimized at an available P level of about 15 mg kg -1 . Slaton et al (2013) suggested that the optimum available P level was 36 -50 mg kg -1 , and that P fertilization scarcely affects the growth in soil with sufficient P. The available P in the soil of the pots was 2.6 mg kg -1 , and that of our experimental fields was 11.7 -16.0 mg kg -1 at Setagaya and 92.8 -150.7 mg kg -1 at Atsugi (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Fertilizer applications to corn in a corn-soybean rotation had inconsistent effects on soybean yield and seed quality. Anthony et al (2012) and Buah, Polito, and Killorn (2000) reported no difference in yield between 0 and 56 kg P ha -1 . However, others have shown increased yields, but at low soil test P levels (Borges & Mallarino, 2000.…”
Section: Soybean Response Following Cornmentioning
confidence: 93%